2015
DOI: 10.1177/1932296814567326
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Acceptability of a Combined Device for Insulin Infusion and Glucose Sensing in the Home Setting

Abstract: For many patients who require insulin, continuous subcutaneous insulin infusion (CSII) offers significant advantages compared to multiple daily injections (MDI). In part because CSII can more closely match the endogenous insulin profile of normal pancreatic β cells, it offers reduced rates of severe hypoglycemia, better metabolic control, and improved quality of life compared to MDI. 1Pumps are often used in conjunction with continuous glucose monitoring (CGM) systems that provide real-time data on glucose con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…27 In fact, the MiniMed Duo combined system achieved adequate clinical CGM accuracy on subjects in a home setting. 28 CGM survival is minimally affected by LH tissue, and CGM sites last longer than infusion sets.…”
Section: Fig 2 (A)mentioning
confidence: 98%
“…27 In fact, the MiniMed Duo combined system achieved adequate clinical CGM accuracy on subjects in a home setting. 28 CGM survival is minimally affected by LH tissue, and CGM sites last longer than infusion sets.…”
Section: Fig 2 (A)mentioning
confidence: 98%
“…The ultimate goal for the treatment of type 1 diabetes is the restoration of physiological blood glucose regulation without the requirement for lifelong therapy such as immunosuppression or immunoregulation. There are numerous challenges for the attainment of this goal, and diverse approaches ranging from insulin pumps to gene therapy to stem cell strategies are all being pursued . In another approach, the replacement of lost islet cells through human islet allotransplantation has established the clinical utility of islet grafting .…”
Section: Introductionmentioning
confidence: 99%
“…29 In clinical trials of SAP, participants rated the device as acceptable. 56 Those on SAP have reported lower diabetes distress, 31,36 higher treatment satisfaction, 31,36 and reduced fear of hypoglycemia. 33 Even in a trial where average use of SAP was roughly 30%, those who stayed with SAP found increased treatment satisfaction and less fear of hypoglycemia.…”
Section: Technology Use and Psychosocial Outcomesmentioning
confidence: 99%